Factors related to the utilization of integrated health services among older people in Kendari City, Southeast Sulawesi Province, Indonesia - Arif, Asmiati; Effendy, Devi Savitri; Muchtar, Febriana; Asfian, Pitrah; Asriati, Asriati (YCAB Publisher & IAKMI SULTRA, 2022)
Background: Integrated health service, called Posyandu, is one of the efforts by the Indonesian Government to improve the health quality of older people. However, its utilization is not optimal. Thus, factors related to it warrant investigation. Objective: This study aimed to identify factors related to the utilization of integrated health services for older people. Methods: This study employed a cross-sectional design among 173 older people aged ≥ 60 registered as members of integrated health services in two areas in Kendari City, Southeast Sulawesi, Indonesia. Convenience sampling was applied, and data were collected from January to March 2022. Result: There was a significant relationship between the older people’s perception (AOR = 2.40; CI = 1.14-5.03; p = 0.018), family support (AOR = 2.73; CI = 1.23-6.02; p = 0.028), and cadres’ role (AOR = 3.62; CI = 1.59-8.21; p = 0.011) with the use of integrated health services. Otherwise, treatment-seeking showed no relation with the utilization of integrated health services (AOR = 1.68; CI = 0.74-3.82; p = 0.094). Conclusion: The significant factors revealed in this study can be used to improve the utilization of integrated health services for older people in the community. Education to change the perception of older people is needed, and family support and cadres’ roles should be advanced to improve healthcare visits in order to increase health quality.